2012
DOI: 10.1038/jes.2012.83
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating socioeconomic and racial differences in traffic-related metrics in the United States using a GIS approach

Abstract: Previous studies have reported that lower-income and minority populations are more likely to live near major roads. This study quantifies associations between socioeconomic status, racial/ethnic variables, and traffic-related exposure metrics for the United States. Using geographic information systems (GIS), traffic-related exposure metrics were represented by road and traffic densities at the census tract level. Spearman's correlation coefficients estimated relationships between socio-demographic variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…While other metrics are available for measuring equity and social disadvantage, these two metrics are chosen because federal environmental justice policies require their consideration (DOT Order 5610.2(a) and Executive Order 12898). Previous studies find that low income and minority residents are disproportionately located in areas near high volume roads or where mobile source air pollutant emissions are higher (Gunier et al, 2003;Houston et al, 2004;Rowangould, 2013;Tian et al, 2013). These studies have often relied on analytical methods that use proximity to roadways or emission inventories as proxies for exposure to mobile source emissions.…”
Section: Resultsmentioning
confidence: 99%
“…While other metrics are available for measuring equity and social disadvantage, these two metrics are chosen because federal environmental justice policies require their consideration (DOT Order 5610.2(a) and Executive Order 12898). Previous studies find that low income and minority residents are disproportionately located in areas near high volume roads or where mobile source air pollutant emissions are higher (Gunier et al, 2003;Houston et al, 2004;Rowangould, 2013;Tian et al, 2013). These studies have often relied on analytical methods that use proximity to roadways or emission inventories as proxies for exposure to mobile source emissions.…”
Section: Resultsmentioning
confidence: 99%
“…The disproportionate distribution of air pollution in areas with low-income and minority populations have created concerns around environmental injustice (54)(55)(56). Several studies have identified socioeconomic and racial disparities in cancer risk from exposure to HAPs, using cancer risk estimates by U.S. EPA NATA program and socioeconomic and demographic data from U.S. Census at census tract level (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals living in high-traffic areas are nonwhite and low income (6), characteristics that are associated with susceptibility to the adverse effects of air pollution. In the United States, an estimated 40 million people live within 100 m of major roads, railways, or airports (7), and millions more commute on major roads, suggesting the importance of exposure to traffic-related air pollutants for public health.…”
mentioning
confidence: 99%